A Civilized Society? The Culture of Punishment in Canada - Hughes, Andrea (Université d'Ottawa / University of Ottawa, 2015)
Punishment is more than a response to criminalized behaviour; at its core, it is a reflection of the cultural, social, and political trends of a society. In Canada, our cultural and emotional sensibilities have long been recognized as producing a moderate and balanced penal system. However, a recent series of ‘tough on crime’ laws and increasingly harsh prison conditions contradict our global reputation for being civil and lenient, and suggest that a period of ‘penal intensification’ (Sim, 2009) is taking place in Canada. This thesis explores Canada’s current penality through a critical, qualitative content analysis of the Safe Streets and Communities Act (2012) legislation and a sample of online public commentary. Drawing on the de/civilizing process theories of Norbert Elias (1939/2000) and John Pratt (1998, 2002, 2011), it is argued that there is a noticeable dominance of de-civilizing discourses and themes found within the legislation and comment boards. While historical developments have arguably made us more “civilized”, the recent implementation of harsh punishments in Canada’s penal system suggests that we are experiencing a “de-civilized” penal intensification.